Development of a hybrid model predicting the mouthfeel of yogurt - Mathmann, Katrin; Kowalczyk, Wojciech; Delgado, Antonio (Journal of Texture Studies, 2009)
Texture perception and mouthfeel are sensory variables that still need further clarification. A reliable method to describe mouthfeel quantitatively by means of physicochemical measurements is missing so far. The current study focuses on a better understanding of the texture perception of yogurt. The final aim of the study consists of the development of a novel hybrid model, which is able to predict mouthfeel sensations objectively. For this purpose, cognitive methods are used in order to merge underlying data pools with respect to process parameters and the composition of dry matter content. These employed data pools result from rheological characterizations as well as sensory analyses of yogurt and from numerical simulations of fluid flow in a simplified anatomical model of the human mouth. This paper introduces the exact procedure of the study. Furthermore, the methods for generating the underlying data pools are described, and the results are presented. © 2009, Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.develo
Keywords: Fluid mechanics; Hybrid cognitive methods; Mouthfeel; Numerical simulations; Sensory analyses